ChemInform Abstract: A Stereoselective Route to Aza‐C‐aryl Glycosides from Arynes and Chiral Nitrones. Issue 14 (20th March 2013) - Khangarot, Rama Kanwar; Kaliappan, Krishna P.
Abstract An efficient strategy for the synthesis of a variety of aza‐C‐aryl glycosides is described.